Where Have They Gone? Recruiting and Retaining Older Rural Research Participants - Elizabeth Grace Nichols; Jean Shreffler-Grant; Clarann Weinert SC (Rural Nurse Organization; Binghamton University, 2021)
Issue: Rural-dwelling elderly have been shown to suffer from health disparities when compared to the general population. Research involving these individuals is important, and to have meaningful results, sample sizes must be adequate. Recruiting and retaining these individuals pose significant challenges. Context: Nurse researchers in the rural northwestern United States conducted a 4-part educational intervention aimed at increasing general and complementary and alternative health care literacy of older rural dwellers. Significant challenges were faced in both recruiting and retaining participants over the 6-month study period. Despite careful planning and community selection, the team had to double the number of communities in which they carried out the project to meet recruitment goals. Retention was also a challenge. Of 127 participants initially enrolled in the study, only 52 remained to the end. Lessons Learned: Challenges of recruiting and retaining are complex and compounded when the target population is rural, older and the study is longitudinal. Recruitment challenges included reaching older adults, offering a compelling program, and offering it in an acceptable format at a convenient time and place. A variety of outreach activities were conducted including in-person presentations, advertising or public interest stories in local newspapers or radio stations, and flyers on bulletin boards in restaurants, clinics, churches, community centers, and libraries. A project champion, an individual well known and connected within the community and committed to the success of the proposed study, is a major asset. Retention strategies included developing relationships with the participants and maintaining contact with them over the course of the study through such mechanisms as appointment cards, e-mail or regular mail, telephone reminders, and thank you cards. Oversampling was important as factors beyond the control of the researcher occurred; for example, illness, death, family crises, unexpected relocations, and weather events that prevented travel to scheduled research events. Keywords: complementary health, health literacy, participant retention, sampling Funding: National Institutes of Health, National Center for Complementary and Integrative Health 1R15AT009097-01 DOI: https://doi.org/10.14574/ojrnhc.v21i1.642